Regulating the catalytic properties of Pt/Al2O3 through nanoscale inkjet printing - Chatziiona, Vasiliki K.; Constantinou, Barbara K.; Savva, Christos S.; Olympiou, Georgios; Kapnisis, Konstantinos; Anayiotos, Andreas; Christophi, Costas A. (My University, 2018)
For the first time ever, a 0.1 wt% Pt/Al2O3 catalyst was prepared by novel inkjet printing and compared against two catalysts prepared by a standard and modified wet impregnation method. The printed catalyst was found to present excellent activity and wide operating temperature window on the selective catalytic reduction of NO by H2 under strongly oxidizing conditions (H2-SCR) in the very low-temperature range of 100–200 °C. The transient studies performed in the present work indicated that the printing process followed led to a unique surface structure of the printed catalyst that probably favors the formation of different active intermediate NOx species, which are active at very low reaction temperatures. Moreover, it was found that the inkjet printing protocol followed resulted in a relatively uniform nano-spherical structure of the developed catalyst.
Keywords: H2-SCR; Inkjet printing; NO reduction; Supported Pt catalysts; TPSR